EVALUATION OF WELLS WATER SUITABILITY OF SOME OASIS AT IRAQI WESTERIN REGION FOR HUMAN AND ANIMAL USES - Ali Hussain I. Al-Bayati; Abdulkarem Ahmed M. Al-Alwany (Journal of Madenat Alelem University College, 2010)
This study was conducted to evaluate wells water suitability of three oasis within Western region of Iraq. They were 98 kilometers(O98) ,Fehadi (OF), and Al-kesheieti (OK) for human and animal uses .Three water samples were collected from every well monthly for one year period for chemical and bacterial analysis and to evaluate water quality for human consumption based on criterion established by American irrigation society . Also ,evaluation was made for their suitability for livestock and domestic animal uses based on proposal guide from FAO. Results for salinity, pH, total hardness , Mg++, K+ anions concentration and micro elements were showed that they are among permitted levels for human uses, but Ca++ concentration was above the permitted level for drink. Which was meaning its necessarily to limited chemical treatment before using these water for drink . While for animal uses all studied parameters results were showed its very accepted for livestock and domestic. The bacteriological study for these waters was indicated that it was very cleans waters and health because we can not diagnosis the coliform in these oasis water.